Livestock farmer’s attitude towards farm telecast programmes - B. SUBRAHMANYESHWARI, C. VIJAYA KUMAR, G.R.K. SHARMA and (The Journal of Research, PJTSAU, 2017)
The technology transfer of science needs to be demonstrated in the language which would be understood by the rural people. Television is considered as an effective tool to disseminate knowledge and information in an easily appreciable way by the needy people in general and farmers of remote area in particular in very short time. The present study was conducted in chittoor district of Andhra Pradesh, with a sample size of 120 respondents. It was found that the majority of the respondents (71.7%) had favourable attitude towards farm telecast programmes, while majority of the independent variables had possessed positive and significant relation with the attitude of the respondents towards various farm telecast programmes. Efforts to make the programmes more interesting in addition to the regularity, interactivity, nativity and location specificity in the farm telecast programmes are expected to bring positive impact on the livestock farming.